Circular Business Model Innovation: Inherent Uncertainties. (17th September 2015) - Linder, Marcus; Williander, Mats
Abstract: Circular business models based on remanufacturing and reuse promise significant cost savings as well as radical reductions in environmental impact. Variants of such business models have been suggested for decades, and there are notable success stories such as the Xerox product–service offering based on photocopiers that are remanufactured. Still, we are not seeing widespread adoption in industry. This paper examines causes for reluctance. Drawing on a hypothesis‐testing framework of business model innovation, we show that circular business models imply significant challenges to proactive uncertainty reduction for the entrepreneur. Moreover, we show that many product–service system variants that facilitate return flow control in circular business models further aggravate the potential negative effects of failed uncertainty reduction because of increased capital commitments. Through a longitudinal action research study we also provide a counterexample to many of the challenges identified in previous studies, which could be overcome in the studied case. Copyright © 2015 John Wiley & Sons, Ltd and ERP Environment